Determination of risk factors contributing to microbial contamination in milk and identification of presence of selected pathogenic bacteria along dairy value chain in Tanga - Shija, F.; Nonga, H.; Kurwijila, Lusato R.; Roesel, Kristina; Grace, Delia; Misinzo, G. (2013)
Contaminated milk is responsible for up to 90% of all dairy-related diseases of humans. A cross sectional study was carried out in Lushoto and Handeni districts of Tanga region to determine handling practices, bacterial contaminations and selected milk-borne zoonotic pathogens along the dairy value chain. A total of 93 respondents were interviewed and subsequently 184 samples of milk and its product were collected for laboratory analysis of total plate count (TPC), coliform plate count (CPC), and detection of Escherichia coli O157:H7 and Brucella abortus using polymerase chain reaction (PCR). Results showed 57% of famers milked their cows under unhygienic conditions and plastic containers were used for storage. Although the mean total plate count was exactly within the East African Standards (EAS, 5.3 log10 cfu/ml) the counts ranged between 3.3 log10 to,5.8 log10 where 87% and 93% of milk from farmers and vendors, respectively, were above the acceptable EAS standards. Meanwhile, 100 % of milk samples were above CPC EAS standards. PCR analyses did not detect E.coli O157:H7 in all the tested milk samples while B. abortus was detected in 37 out of 87 samples tested (42.5%). It was concluded that limited veterinary/extension services, unhygienic practices of milking and post-harvest handling along the dairy value chain possibly contributed to microbial contamination of milk. Detection of B. abortus in milk is of public health significancy due to its zoonotic potential. It is recommended that veterinary/extension services should be provided to livestock farmers on proper animal husbandry and control of diseases.